GIS-material for the archaeological project: Prehistoric settlement remains along a power line in south-east Åtvidaberg_2 - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to reconstruction of the power grid between mellan Åtvidaberg and Broddebo and on the property Domra in Västervik municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed several preliminary investigations and stage 2 surveys in Gullebo, Mosshult and Broddebo, Gärserum parish, Åtvidaberg municipality, during summer and autunm of 2005. Two surveys have previously been performed in the area, in connection with rebuilding of the National Road 35. Prehistoric remains, such as graves, were discovered nearby the village sites of Gullebo, Mosshult och Broddebo during these surveys, as well as several potential settlement locations. The result showed a settlement site just north of Broddebo village. The current survey found, among other things, two hearths and a possible agricultural layer damaged by ploughing. UV Öst suggests no further archaeological measures since the trenching for the power lines could be made without affecting the archaeological remains.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation and the stage 2 survey, was to determine whether any archaeological remains were going to be affected by the planned trenching and, if possible, to try to avoid them. The results were going to form the basis for possible future decisions by the County Administrative Board concerning the matter.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har under sommaren och hösten 2005 gjort arkeologiska förundersökningar och utredningar, etapp 2, i Gullebo, Mosshult och Broddebo, Gärserums socken, Åtvidabergs kommun. Anledningen är att exploatören företagit en ombyggnation av kraftledningsnätet mellan Åtvidaberg och Broddebo samt till fastigheten Domra i Västerviks kommun. I området för kabelsträckningen har tidigare två utredningar utförts i samband med inventeringsarbeten för Riksväg 35. Dessa visar bland annat på förekomst av förhistoriska lämningar, såsom gravar, i närheten av de gamla bytomterna Gullebo, Mosshult och Broddebo. Utredningarna pekar dessutom ut ett antal topografiskt lämpliga boplatslägen.
Resultatet visade på ett område med förekomst av förhistoriska boplatslämningar strax norr om Broddebo by. Den nu aktuella utredningen kunde visa på bland annat förekomst av två härdar samt ett sannolikt nerodlat boplatslager. UV Öst föreslår inga vidare åtgärder då det aktuella ledningsschaktet kunde dras på sådant sätt att de lämningar som framkom vid utredningen kunde undvikas.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen och den arkeologiska utredningen, etapp 2, var att fastställa huruvida fornlämningar kom att beröras av det planerade schaktningsarbetet och om möjligt försöka undvika dem. Eventuella resultat skulle sedan ligga till grund för Länsstyrelsens bedömning ifall ytterligare beslut enligt KML skulle komma att krävas.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Förhistoriska boplatslämningar längs en starkströmskabel i sydöstra Åtvidaberg_2
Keywords: prehistoric time; förhistorisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi